Electrochemical behaviour of Vanadium(V) on electrochemically synthesized magnetite film electrodes - Dabrowski, Sergio Gustavo (2018)
In this work, the electrochemical response of Vanadium(V) species on magnetite film electrodes is investigated. Magnetite is deposited electrochemically on glassy carbon electrodes, with an intermediate layer of poly(thiophene) to avoid water infiltration. These electrodes show good reproducibility and stability up to pH = 2.0. Mononuclear V(V) species show low electroactivity on this surface. Cyclic voltammetry at low V(V) concentration shows that it is electroactive only at pH < 3. i.e. as VO2 +. A single reduction peak is observed at ~− 0.7 V vs SCE (at 50 mV s− 1), and an oxidation one at ~ 0.5 V vs SCE, indicating high irreversibility of the V(V)/V(IV) couple; these peaks are found to be solution phase reactions. These features are interpreted in terms of mononuclear V species. At higher V concentrations, where polymeric V(V) species are dominant, a somewhat higher electroactivity is observed, with two reduction peaks and two/three oxidation peaks.